John Company: The Act of Incorporation. Issue 1 (April 2020) - Ashford, David
Abstract : 'John Company: The Act of Incorporation' is the first episode in a series of twelve open-form pieces on the history of the British East India Company, and relates legal innovations behind the inception of the Company to the development of forms of Artificial Intelligence in Elizabethan England. The poem references primary material contained in the seventeenth-century anthology Purchas his Pilgrimes and in the East India Company's archives now housed in the British Library, and draws on research conducted by Kevin LaGrandeur in his book Androids and Intelligent Networks in Early Modern Literature and Culture (Abingdon, Oxon: Routledge, 2013), and by Vladimir I. Braginsky in his essay 'Towards the Biography of Hamzah Fansuri: When Did Hamzah Live? Data From His Poems and Early European Accounts', Archival 57 (Paris, 1999), 135–75.